Class II Hybrid Organic-inorganic Membranes Creating New Versatility in Separations - Meynen, Vera; L. Castricum, Hessel; Buekenhoudt, Anita (Current Organic Chemistry, 2014)
Membrane technology is becoming more important as a low energy separation process that can replace or enhance the efficiency of currently often costly and energy-consuming separation processes. After an introduction on the potential of hybrid materials for membranes, we highlight and categorize the wide diversity of hybrid organic-inorganic membranes. In this review, we focus on the preparation and application of class II hybrid organic-inorganic membranes with mechanically stable inorganic supports. Class II points to the presence of covalent bonds between organic and inorganic moieties. The variety of synthesis approaches applied to prepare such separation layers can be divided into 2 types, i.e. direct coating of a pre-formed hybrid solution, and post-synthesis grafting of organic groups. In the last part, we focus on strategies delivering hybrid organic-inorganic membranes that show promise for enhanced molecular separations in gas separation, hydrophilic and organophilic pervaporation and organic solvent nanofiltration. In addition, we will discuss the use of organically modified inorganic RO (reverse osmosis), UF (ultrafiltration) and MF (microfiltration) membranes for ameliorated pressure driven water filtration, membrane contactors, and low-fouling oil/water separation.
Keywords: synthesis methods